Expérience communautaire pour les hommes pédophiles - Daigle, Marc (Criminologie, 1997)
The evaluation of the self-help program "Le groupe d'entraide Amorce" for pedophilic men showed they were progressing regarding certain pedophilic characteristics, particularly with respect to a better integration of their adult sexuality. However, nobody in this program claimed to be "treating" pedophilia directly. In fact, all of them relied upon the sharing and supporting dynamics of a self-help group to face other related problems and to reach the preliminary but necessary steps for deeper changes. The beneficial effect of the program was felt regarding mainly stopping withdrawal, changing attitudes, increasing empathy, motivating for change, improving communication skills, discharging emotions, clarifying immediate problems, repositionning as adults, supporting when depressed or decreasing anxiety. The triangulation of the points of view of facilitators, external parties, and participants did confirm these results both regarding pedophilia and other problems. Beyond these effects, the evaluation showed that the main strengths of the program were: the support and sharing of experiences between participants ; the motivation and availability of those involved ; the openness to external critics, novelty, uniqueness, pro-gressiveness, communal, non-medical, and preventive approach of pedophilia ; and the respect for and "responsibilisation" of the participants. Some aspects of the program also needed to be improved and specific recommendations were provided to the administrators.